ChemInform Abstract: Advances in Cathode Materials for Solid Oxide Fuel Cells: Complex Oxides Without Alkaline Earth Metal Elements. Issue 29 (June 2016) - Chen, Yubo; Zhou, Wei; Ding, Dong; Liu, Meilin; Ciucci, Francesco; Tade, Moses; Shao, Zongping
Abstract: Review: 469 refs.